1993
DOI: 10.1029/93wr00496
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive set of analytical solutions for nonequilibrium solute transport with first‐order decay and zero‐order production

Abstract: Solute transport in the subsurface is often considered to be a nonequilibrium process. Predictive models for nonequilibrium transport may be based either on chemical considerations by assuming the presence of a kinetic sorption process, or on physical considerations by assuming two‐region (dual‐porosity) type formulations which partition the liquid phase into mobile and immobile regions. For certain simplifying conditions, including steady state flow and linear sorption, the chemical and physical nonequilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
147
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(152 citation statements)
references
References 20 publications
1
147
0
4
Order By: Relevance
“…The two-region non-equilibrium model (2RNE; Toride et al 1993) was initially developed for porous media, where partitioning of solutes between mobile water in the centres of the large pores and immobile water in fine pores or adsorbed to mineral surfaces can be observed. Field and Pinsky (2000) demonstrated that this model could also be applied to karst aquifers, where rapid flow velocities occur in the centres of active conduits (mobile fluid region), while flow velocities are much slower at the conduit margins, in adjacent fractured rock volumes, but also in eddies and pools, and in the pores of cave sediments (immobile fluid region).…”
Section: Modelling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-region non-equilibrium model (2RNE; Toride et al 1993) was initially developed for porous media, where partitioning of solutes between mobile water in the centres of the large pores and immobile water in fine pores or adsorbed to mineral surfaces can be observed. Field and Pinsky (2000) demonstrated that this model could also be applied to karst aquifers, where rapid flow velocities occur in the centres of active conduits (mobile fluid region), while flow velocities are much slower at the conduit margins, in adjacent fractured rock volumes, but also in eddies and pools, and in the pores of cave sediments (immobile fluid region).…”
Section: Modelling Approachmentioning
confidence: 99%
“…2). Reactive processes such as retardation and degradation, can also be included (Toride et al 1993) and were already implemented for karst aquifers (Geyer et al 2007), but are not relevant in this case. In karst conduits, dispersion is often most relevant in the flow direction so that one-dimensional models represent a legitimate simplification.…”
Section: Modelling Approachmentioning
confidence: 99%
“…Boundary condition 2 Genuchten and Alves (1982, p. 31 Genuchten and Alves (1982) pp. 32 Genuchten and Alves (1982, p. 63 Genuchten and Alves (1982, p. 60 Toride et al (1993) Initial condition (t = 0)…”
Section: Boundary Conditionmentioning
confidence: 99%
“…32 Genuchten and Alves (1982, p. 63 Genuchten and Alves (1982, p. 60 Toride et al (1993) Initial condition (t = 0)…”
Section: Boundary Conditionmentioning
confidence: 99%
“…It is directly affected by heterogeneity in flow and can, therefore, help to assess nonuniformity in surface and soil profile flow introduced by crop production practices. Solute dispersivity can be determined by fitting a solution of the onedimensional convective-dispersive equation (CDE) to observed soil solute resident concentrations established in response to controlled boundary conditions (Toride et al, 1993). The model has been successfully applied at both the column scale (Wierenga and van Genuchten, 1989) and the field scale (Biggar and Nielsen, 1976;Roth et al, 1991).…”
mentioning
confidence: 99%